1996
DOI: 10.1044/jshr.3903.468
|View full text |Cite
|
Sign up to set email alerts
|

The Specific Relation Between Perception and Production Errors for Place of Articulation in Developmental Apraxia of Speech

Abstract: Developmental apraxia of speech is a disorder of phonological and articulatory output processes. However, it has been suggested that perceptual deficits may contribute to the disorder. Identification and discrimination tasks offer a fine-grained assessment of central auditory and phonetic functions. Seventeen children with developmental apraxia (mean age 8:9, years:months) and 16 control children (mean age 8:0) were administered tests of identification and discrimination of resynthesized and synthesized monosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1
4

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 37 publications
4
36
1
4
Order By: Relevance
“…Empirical data indicate that there is a close relation between production symptoms and perceptual acuity in children with speech sound disorders (SSD): poor perceptual performance is related to poor production performance (Edwards, Fox, & Rogers, 2002;Groenen, Maassen, Crul, & Thoonen, 1996;Maassen, Groenen, & Crul, 2003;Nijland, 2009;Raaymakers & Crul, 1988). Computer simulations with the DIVA model suggest that the ability for auditory self-monitoring might influence the nature of speech-motor deficits during development .…”
Section: Developmental Speech Sound Disordermentioning
confidence: 97%
“…Empirical data indicate that there is a close relation between production symptoms and perceptual acuity in children with speech sound disorders (SSD): poor perceptual performance is related to poor production performance (Edwards, Fox, & Rogers, 2002;Groenen, Maassen, Crul, & Thoonen, 1996;Maassen, Groenen, & Crul, 2003;Nijland, 2009;Raaymakers & Crul, 1988). Computer simulations with the DIVA model suggest that the ability for auditory self-monitoring might influence the nature of speech-motor deficits during development .…”
Section: Developmental Speech Sound Disordermentioning
confidence: 97%
“…Unlike adults, whose apraxia was acquired after the developmental period for speech-language acquisition, the stress de® cits in the children with AOSci in this study presumably re¯ect di culty or delays in the acquisition of English stress rules. Some investigators have reported impaired auditory processing skills in children with suspected AOSc (e.g., Robin, Hall, and Jordan, 1986;Groenen, Maassen, Crul, and Thoonen, 1996 ). De® cient auditory or auditory-temporal processing could aOE ect both the initial decoding and eventual representation of metrical forms, as well as the on-line encoding and self-monitoring of appropriate sentential stress.…”
Section: Linguistic Perspectivesmentioning
confidence: 99%
“…Electrical recordings, magnetic record ings, animal studies, and lesion studies point to a major origin on the superior surface of the temporal lobe in the auditory cortex [3,4], The P300 is considered to represent a more general cognitive response that originates from multiple auditory and nonauditory structures [5], Measuring MMN seems especially useful when testing subjects with problems of speech processing. Groencn et al [6,7] and Locke [8] in addition to others have demonstrated that speech perception problems are rarely of a general nature, but concern specific speech features. For the perception of consonants, three important dimensions arc considered for choosing speech contrasts: voicing, place of articulation, and manner of articulation.…”
Section: Introductionmentioning
confidence: 99%